THE RELATIONSHIP OF STUDENTS’ METACOGNITIVE READING STRATEGIES AWARENESS AND READING COMPREHENSION: THE CASE OF THE SIXTH SEMESTER STUDENT OF ENGLISH DEPARTMENT UNIVERSITAS NEGERI PADANG (UNP) - Zuledwi Wahyuni; Ratmanida Ratmanida; Leni Marlina (Universitas Negeri Padang, 2018)
This study is about the relationship of students’ metacognitive reading strategies awareness and reading comprehension: the cast of sixth semester students of English Department Universitas Negeri Padang (UNP). Since it is still doubted whether or not there is a significant correlation between the students’ Metacognitive Reading Strategies Awareness and Reading Comprehension, the writer conducted a research to obtain the answers to those questions. Prior to finding out relationship, the study tried to ascertain the level awareness and types strategies that respondents use when they read English academic texts, and their reading performance. Using SORS questionnaire and Test TOEFL with students’ k1-15 English department (UNP), the study found out that the awareness of respondents on using metacognitive reading strategies is on medium level. From three categories of metacognitive reading strategies, the Problem-Solving Strategies (PROB) is the most frequently used by respondents. On the level reading comprehension, the respondents got below average or low level. For correlation, the study used Pearson product correlation moment. The study reveals that there is no correlation between metacognitive reading strategies awareness and reading comprehension.